The Effect of Accounting Control and Management Control on Managerial Performance Through Participation in Budget Preparation as an Intervening Variable at PT. GARAM (Persero) - Antoro, Eko Wahyudi; Supriyadi, Stevanus Gatot; Astari, Ita Yoeli (Universitas Airlangga, 2024)
A business may be defined as an organizational structure that employs human, natural, and other economic resources to fulfill its aims. Human resources in an organization are one of the most important factors determining organizational effectiveness; as a result, every company requires a management control system, accounting control, and active participation in budget preparation with the goal of regulating organizational activities through organizational leaders so that they are consistent with the company's objectives. The purpose of this research is to analyze and assess the effect of management and accounting controls on budget preparation participation and managerial performance. This research technique uses a quantitative and associative approach. The study's participants were all PT. Garam (Persero) managers. The sampling strategy then used census or analytic methods to choose 49 managers from the overall population. The analytical method employs structural equation modeling analysis using partial least squares (PLS) 4 software tools, as well as mediation testing using the sobel test calculator. The test results showed that the accounting control variable had a significant impact on budget preparation participation but not management performance. The management control variable did not have a significant influence on either budget preparation participation or managerial performance. Meanwhile, the engagement variable in budget preparation has been found to have a significant impact on managerial performance. Furthermore, this study discovered that budget participation variables act as a moderator in the relationship between accounting control variables and managerial performance, which contradicts the relationship between management control variables and managerial performance.